The Use of Money in Society: Friedrich Hayek's Social Work. (October 2021) - Swanson, Jacob
Recent studies of Friedrich Hayek have focused on his theorization of spontaneous order and its relationship to his views on freedom and market individualism. For many scholars, the impersonal nature of Hayek's spontaneous order, which optimally coordinates human action without human coordination, and/or Hayek's contention that freedom consists of the exercise of individual choice in a market, reveals Hayek's neoliberal project to replace or erase the social domain of human life and activity. This article makes the claim that two different, but related, versions of the social exist in Hayek's writings. The logic of his first and prominent view of social order as spontaneous order depends, I argue, upon a second account of the social, found in Hayek's writings on money, which consists of forms of conscious and collective social integration and subject formation that the first view requires but cannot account for. In this way, Hayek's social order is sustained not spontaneously but by money-based collective activities and social(ized) subjectivities that make it possible, and his neoliberal project thus depends on fundamental, if disavowed, connections between the social and the political.